Occurrence of helminths and coccidia from calves in a commercial farm in Kuantan, Pahang, Malaysia - Mat Yusof, Afzan; Mohammad, Mardhiah; Hisamuddin, Nur Hazirah; Hashim, Najat; Soffian, Sharmeen Nellisa; Md Isa, Muhammad Lokman (2016)
Parasitic infections in cattle are considered one of the major problems in livestock industry causing morbidity and mortality. Hence, the study aimed to determine the occurrence of intestinal helminths and coccida from cattle in a commercial farm in Kuantan, Pahang between April to May 2015. The fecal samples were collected and examined using floatation and sedimentation methods. A total of 152 calves aged 1 year old and reared under intensive farm management were examined for helminths and coccidia. Results showed that 13 calves were infected with helminths which include Strongyle (7.24%) and followed by Strongyloides (1.32%). Meanwhile, 84 calves were infected with coccidia, Eimeria species (55.26%). From this result, Eimeria species were more dominant in calves than helminths. The present findings indicate that Eimeria species infection could be a problem of calves kept in crowding and under intensive management system. Hence, a better control and strategies should be implemented to control Eimeria species infection among calves.